Prevention and treatment strategies for kidney transplant recipients in the context of long-term existence of COVID-19 - Zheng, Zeyuan; Sun, Huimin; Hu, Xiaoyan; Xuan, Zuodong; Fu, Meiling; Bai, Yang; Du, Yifan; Liu, Bin; Sui, Xiuyuan; Zheng, Jianzhong; Shao, Chen (Frontiers in Medicine, 2024)
The sudden outbreak of coronavirus disease 2019 (COVID-19) in early 2020 posed a massive threat to human life and caused an economic upheaval worldwide. Kidney transplant recipients (KTRs) became susceptible to infection during the COVID-19 pandemic owing to their use of immunosuppressants, resulting in increased hospitalization and mortality rates. Although the current epidemic situation is alleviated, the long-term existence of COVID-19 still seriously threatens the life and health of KTRs with low immunity. The Omicron variant, a highly infectious but less-pathogenic strain of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has raised concerns among transplant physicians regarding managing KTRs diagnosed with this variant. However, currently, there are no clear and unified guidelines for caring for KTRs infected with this variant. Therefore, we aimed to summarize the ongoing research on drugs that can treat Omicron variant infections in KTRs and explore the potential of adjusting immunotherapy strategies to enhance their responsiveness to vaccines. Herein, we discuss the situation of KTRs since the emergence of COVID-19 and focus on various prevention and treatment strategies for KTRs since the Omicron variant outbreak. We hope to assist physicians in managing KTRs in the presence of long-term COVID-19 variants.